EKSISTENSI MANUSIA DALAM FILM “AISYAH BIARKAN KAMI BERSAUDARA” KARYA HERWIN NOVIANTO - Susiati Susiati (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This study aims to describe human existence in the film “Aisyah Biarkan Kami Bersaudara” by Herwin Novianto. This research is a qualitative research. Data is collected using the audio visual method, namely by seeing and hearing an object from images and sounds. Meanwhile, data collection techniques use the refer and note technique. Data were analyzed descriptively in accordance with Koeswara's human existence concept theory which included four types, namely togetherness and love, opposition, alienation and loneliness, and death. The results showed that the concept of human existence in the film “Aisyah Biarkan Kami Bersaudara” by Herwin Novianto have three, namely (1) the concept of togetherness and love, including intimacy, mutual assistance/cooperation, advising, mutual respect and respect, attention, responsibility, openness, compassion, tepa salira, belief, and joke; (2) the concept of conflict, including disagreement, disagreement, disrespect, acceptability, distrust, and hatred; (3) the concept of alienation and loneliness, including sadness, anxiety, aggravation, worry, fear, and lies.